Optimization and Kinetic Study of Ende-Natural Zeolite as Candidates of Ammonia Adsorbent on Broiler Chicken Litter - Abner Tonu Lema; Cytske Sabuna; Yehezkial Wila Balu (KOVALEN: Jurnal Riset Kimia, 2022)
Zeolite Natural Ende (ZNE) is a local material from Ende, East Nusa Tenggara which can be used as an adsorbent candidate to reduce environmental pollution due to poultry farm wastes. The purpose of this study is to obtain optimal conditions and adsorption kinetics of ZNE as an adsorbent in terms of absorbing NH3, water content, and neutralizing pH on broiler litter. This study consisted of 3 stages such as sample preparation, optimization of acid concentration, particle size, contact time, adsorbate concentration, as well as determination of ZNE-methylene blue adsorption kinetics. The results of the analysis revealed that the best conditions are using 1 M H2SO4, particle size 80 mesh, contact time for 30 minutes with an adsorption capacity of 1.999 mg/g, and methylene blue 80 ppm as an optimal condition. Furthermore, ZNE-methylene blue adsorption kinetics model is the second order type 1 kinetics by R2 = 1, and also adsorption rate constant is 0.0019 g.mg-1.min